Drum Groove Corpora - Hosken, Fred; Bechtold, Toni; Hoesl, Florian; Kilchenmann, Lorenz; Senn, Olivier (Empirical Musicology Review, 2021)
Patterned microtiming deviations from metronomic regularity are ubiquitous in the performance of metered music. The relevance of microtiming to the perception of music has been studied since the 1980s. Most recently, microtiming has been investigated as a cause of groove (i.e., the pleasant urge to move in response to music). The study of microtiming relies on the availability of microtiming data. This report presents three large corpora of onset timings derived from drum kit performances in popular Anglo-American popular music styles. These data are made freely available (CC 4.0 license) to provide a resource for use by analysts and experimenters alike. They offer a common point of reference for future studies into the temporal facets of music performance. The datasets adhere to FAIR principles; they thus facilitate replication of analyses and experimental stimuli.